Reading Strategies Used by College English Students - Fitrawati Fitrawati; Hermawati Syarif (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2021)
The research was aimed to acknowledge and know the reading strategies and in what stage the students mostly used reading methods by English Language and Literature major students, English Department, Universitas Negeri Padang. This research used descriptive quantitative. The population was the students who had taken and passed Basic Reading, Intermediate Reading, Advanced Reading, and Critical Reading and the sample of the research was 228 students of the total population. In collecting the data, the researcher asked the students to fill out the questionnaire given by the researcher. The results were divided into three divisions and they were pre-reading strategies, while-reading strategies, and post-reading strategies. It was found the pre-reading strategies had 66.62%, whilst-reading strategies was 71.59%, and post-reading strategies was 69.45%. It had indication that the students were aware of the strategies in reading and they had tendency to implement all of the strategies in reading English.